TREX1 activators: A novel therapeutic strategy for rheumatoid arthritis management via cfDNA clearance - Yuping Wang; Weidan Luo; Wanyu Wu; Chang Chen; Bo Qin; Xiongfei Xu; Yulin Xu; Jianghuiyi Zeng; Linna Wang; Jiujie Yang; Jerome P.L. Ng; Wuyan Zheng; et al. (Pharmacological Research, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by systemic inflammation and progressive joint destruction. Although current treatments, including conventional disease-modifying antirheumatic drugs (DMARDs) and biologics, offer therapeutic benefits, they are often associated with drug resistance and significant adverse effects with long-term use. Our previous research identified the accumulation of circulating cell-free DNA (cfDNA) as a critical pathogenic factor in RA, contributing to immune dysregulation and sustained inflammatory responses. TREX1, a key 3′-5′ exonuclease responsible for degrading cytoplasmic DNA fragments, has been implicated in alleviating RA symptoms by promoting cfDNA clearance. In this study, we investigated the therapeutic potential of two natural compounds, pterostilbene (PTE) and bilobalide (BB), as novel TREX1 activators, and evaluated their anti-inflammatory efficacy in RA. Our results demonstrated that both PTE and BB significantly upregulated TREX1 expression, reduced cfDNA accumulation and cGAS–STING pathway activation, and ameliorated inflammation in the adjuvant-induced arthritis (AIA) rat model. In TREX1 conditional knockout models, these therapeutic effects were markedly attenuated, underscoring the central role of TREX1 in mediating their anti-inflammatory actions. Importantly, the combination of PTE and BB exhibited a synergistic effect, further enhancing cfDNA degradation and suppressing pro-inflammatory cytokine production. These findings suggest that targeting endogenous cfDNA clearance via TREX1 activation represents a promising therapeutic strategy for RA, with broader implications for other autoimmune and age-related inflammatory diseases.